Normative Analysis and Moral Education: How May We Judge? - Burns, David P. (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2008)
The viability of philosophy of education as a distinct and valued field of inquiry in educational research is under significant threat. While the debate over the proper role and value of philosophy of education continues, courses and faculty positions in philosophy of education become increasingly rare. I advance the view that this situation requires philosophers of education find new ways to bring their work to practicing educators. I propose a particular kind of normative analysis, within the context of moral education, as one way to bring valuable philosophic work to the daily practice of teaching. It is argued that the use of normative criteria, comprised of certain key characteristics for moral education, can serve not only as valuable analytic tools but may also draw practicing educators into conversations that generally take place between philosophers of education in the academy.